Analisis Pengaruh Budaya Organisasi dan Sistem Tanggung Renteng terhadap Perilaku Anggota yang berdampak kepada Keamanan Usaha di Koperasi Setia Budi Wanita Malang - Savitri Sartono; Harianto Respati (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2021)
This research examines, analyzes, and examines the influence of organizational culture and shared responsibility systems on member behavior that impacts on business security in the Setia Budi Wanita Cooperative (SBW) Malang, East Java, Indonesia. Researchers are interested in examining this by seeing that there is something unique and great in the SBW Malang Cooperative in terms of organizational culture, shared responsibility systems, member behavior, and business security so that researchers consider it necessary to conduct research to determine the influence of organizational culture and systems joint responsibility for member behavior that impacts on business security in the Malang SBW Cooperative.